Infestaciones múltiples por «Tenia saginata» - Greenway, Daniel (1937)
The author reviews the recorded cases of persons, with multiple Taenia saginata, and adds to the sophistical reasoning of the case an individual, who died of cancer of the suprarenal capsule, and in whose autopsy, a mass was found in the small intestine, consisting of nine Taenias, complete with their respective scolex (head), neck and proglottides (segments).